Dynamic Capability on Business Performance through Ambidextrous Innovation in The Coffee Business - Rachmawati, Eva; Gaffar, Vanessa; Wibowo, Lili Adi; Dirgantari, Puspo Dewi (Majalah Ilmiah Bijak, 2025)
Objectives: In the context of rising global competition and shifting consumer demands, coffee enterprises face increasing pressure to innovate while maintaining consistent business performance. This study investigates the role of dynamic capabilities in enhancing business performance through the mediating mechanism of ambidextrous innovation within the Indonesian coffee industry. Methodology: Adopting a quantitative, explanatory research design, the study collected primary data from 362 decision-makers representing various types of coffee businesses, including cafés, roasteries, and producers. Using structural equation modeling with Partial Least Squares (PLS-SEM), the study tested both direct and indirect relationships among dynamic capabilities, ambidextrous innovation, and business performance. Finding: The findings reveal that dynamic capabilities—specifically sensing, seizing, and reconfiguring—positively influence both exploitative and explorative innovation strategies, which in turn significantly improve multiple dimensions of business performance. Moreover, ambidextrous innovation was found to partially mediate the relationship between dynamic capabilities and performance outcomes, underscoring its strategic importance in resource-constrained environments. The study contributes to the theoretical development of dynamic capabilities and innovation management by extending the application of Conservation of Resources (COR) Theory to the context of small and medium-sized enterprises in emerging markets. Conclusion: It also offers practical insights for managers and policymakers seeking to foster innovation-driven growth in the agri-food and service sectors.